Development of an IoT Embedded Wearable Device with Non-Contact Temperature Detector for Early Detection of Fever - Azman, Nayli Nabila; Mohd Addi, Mitra; Al-Abed, Amr (International Journal of Integrated Engineering, 2023)
One of the most common and early symptoms of any viral infections is fever which is the reaction to a disease-specific stimulus causing the increase of human body temperature. The current common method of monitoring the human body temperature uses the application of non-contact infrared thermometer (NCIT) and is only limited for stationary conditions within short distances and mostly suitable for indoor premises. The available technology to detect human body temperature for longer distances uses the thermal camera which is costly and large. Thus, it is challenging to detect anyone with high body temperature in non-stationary conditions, at longer distances, especially outdoor. The paper proposes an innovation to the current practice, for a wearable non-contact temperature detector device which is portable. The wearable non-contact temperature detector embeds a thermal sensor and a microcontroller to a normal hat. It is able to detect objects with higher temperature (37.5 °C) within 1 meter radius of 60° angle view in stationary and non-stationary conditions. The wearable device communicates via Bluetooth to a mobile device to display the detected temperature and notifies the user via alert message and alarm for high temperature detection. Display of the object’s thermal image is also available with a resolution of 8 8 pixel. The wearable non-contact temperature detector is able to achieve 99% accuracy of temperature measurement for detection distance of up to 70 cm for indoor and within 20 cm for outdoor when tested with normal temperature subject and high temperature objects and compared with the actual temperature detected via a commercial NCIT device.